2010
DOI: 10.1007/s00702-009-0358-y
|View full text |Cite
|
Sign up to set email alerts
|

BuChE K variant is decreased in Alzheimer’s disease not in fronto-temporal dementia

Abstract: Alzheimer's disease (AD) is characterized by a significant reduction in AcetylCholinesterase and an increase in ButyrylCholinesterase (BuChE) activity. The existence of polymorphic regions on the BuChE gene has been previously described; the most frequently found polymorphism is the so-called K variant, which leads to a 30% decreased enzymatic activity. Different studies reported a positive association between K variant and AD, strongest among late-onset AD and Apolipoprotein E (APOE) e4 carriers. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…But differed significantly of studies such as Bizzaro et al [21], which suggest a protective effect of K variant for AD, and differed also of surveys that suggest K variant as a risk factor for AD [22,23]. Podoly et al [24] considered that the controversial results are due to biochemical properties of variant K, which may have ambiguous effect on AD because the same structural features that destabilize BChE variant K are those that make it less effective as a neuroprotector.…”
Section: Discussionmentioning
confidence: 93%
“…But differed significantly of studies such as Bizzaro et al [21], which suggest a protective effect of K variant for AD, and differed also of surveys that suggest K variant as a risk factor for AD [22,23]. Podoly et al [24] considered that the controversial results are due to biochemical properties of variant K, which may have ambiguous effect on AD because the same structural features that destabilize BChE variant K are those that make it less effective as a neuroprotector.…”
Section: Discussionmentioning
confidence: 93%
“…Some of them found the BCHE-K was associated with AD (Lehmann et al, 1997;McIlroy et al, 2000;Raygani et al, 2004;Tilley et al, 1999;Wiebusch et al, 1999) and others found no association (Alvarez-Arcaya et al, 2000;Ki et al, 1999;Singleton et al, 1998). Bizzarro et al (2010), in turn, suggest a protective effect of K variant, since the authors found it in a lower frequency in AD patients when compared to healthy controls and to fronto-temporal dementia (FTD) patients. In contrast to Podoly et al (2009), in the present study it was verified that the K variant acts by reducing G2, G1 and G1-ALB relative activities and not the tetramer (G4), which suffered greater influence of AD itself.…”
Section: Discussionmentioning
confidence: 94%
“…Some researchers18,3235 found association between the BChE -K and AD, whereas others17,36 found no association. Alvarez-Arcaya et al11 and Bizzarro et al37 suggested a protective role of BChE -K. The correlation of BChE-K with MCI as well as AD is different between different ethnic groups. Thus, BChE-K may be either a risk or a protective factor in AD 38.…”
Section: Discussionmentioning
confidence: 98%